2021
DOI: 10.3390/toxins13040264
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Consistent, Reproducible Botulinum Toxin Type A Dosing Method for Upper Limb Tremor by Kinematic Analysis

Abstract: Botulinum toxin type A (BoNT-A) injection patterns customized to each patient’s unique tremor characteristics produce better efficacy and lower adverse effects compared to the fixed-muscle-fixed-dose approach for Essential Tremor (ET) and Parkinson’s disease (PD) tremor therapy. This article outlined how a kinematic-based dosing method to standardize and customize BoNT-A injections for tremors was developed. Seven ET and eight PD participants with significant tremor reduction and minimal perceived weakness usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As a result, Torqway can be used to improve overall body mobility and overall fitness. The highest ROM values were obtained for the following movements: elbow joint flexion, shoulder joint abduction, shoulder joint flexion [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. The lowest ROM values were obtained for lower limb and spine movements.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, Torqway can be used to improve overall body mobility and overall fitness. The highest ROM values were obtained for the following movements: elbow joint flexion, shoulder joint abduction, shoulder joint flexion [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. The lowest ROM values were obtained for lower limb and spine movements.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial (NCT02207946), 30 patients were randomized and followed up to 24 weeks after treatment, overall finding that BoNT injections decreased tremor severity and improved hand motor function with a favorable tolerability profile [9]. This study also showed that tremor kinematic analytics technology could be successfully scaled for use in other clinical sites, a topic that the same group discussed in greater detail in another article of this issue [10].…”
mentioning
confidence: 88%
“…With the development of science and technology and the depth of related research, researchers have found that observing technical movements using the naked eye or the analysis of back handspring movements based on experience is not scientific, accurate and objective enough. In the literature [7], the kinematic analysis of Zou Kai's single-bar parallel-leg Makelov maneuver was carried out using high-speed photography and three-dimensional image analysis. A kinematic technical model was established to test the kinematic characteristics of outstanding athletes completing the single-bar parallel-leg Makelov maneuver according to the part of gymnastic rules and sports biomechanics principles.…”
Section: Introductionmentioning
confidence: 99%